The Politics of Consumer Education Materials Used in Adult Literacy Classrooms - Jennifer A. Sandlin (Adult Education Research Conference, 1999)
This study examined consumer education texts used in adult literacy programs to see how they portray adult literacy students as consumers and the consumer market. It was concluded that the hidden curriculum of the texts promotes reproduction of class inequalities.